2017
DOI: 10.1111/his.13166
|View full text |Cite
|
Sign up to set email alerts
|

Clonal reticulohistiocytosis of the skin and bone marrow associated with systemic mastocytosis and acute myeloid leukaemia

Abstract: Here, we provide circumstantial evidence to suggest that at least a subset of cutaneous reticulohistiocytoses harbour clonal molecular alterations. Furthermore, we confirm that these lesions have the potential to arise in the setting of concurrent haematological disorders. In this hypothesis-generating study, two possible tumorigenesis models are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…1,[11][12][13] Giant cells may display emperipolesis of neutrophils or lymphocytes. 9 Lesions involving other tissues such as synovia, gastrointestinal mucosa, pleura or bone marrow show identical features with a lower number of giant cells. 14 In MR, fragmentation and phagocytosis of collagen (collagenophagocytosis) are reported in some cases.…”
Section: Histopathological and Immunohistochemical Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…1,[11][12][13] Giant cells may display emperipolesis of neutrophils or lymphocytes. 9 Lesions involving other tissues such as synovia, gastrointestinal mucosa, pleura or bone marrow show identical features with a lower number of giant cells. 14 In MR, fragmentation and phagocytosis of collagen (collagenophagocytosis) are reported in some cases.…”
Section: Histopathological and Immunohistochemical Findingsmentioning
confidence: 99%
“…In 2017, Fusco et al reported the case of a RH clonally related to an acute myeloid leukaemia (both harbouring a t(1;9)) providing for the first time evidence for a clonal origin of RH. 9 In 2019, Bonometti et al described the presence of the BRAFV600E mutation in a case of disseminated RH, 10 whereas Murakami and colleagues highlighted the presence of two possible driver mutations (i.e. mutations in MAP2K1 and TET2 genes) in one MR patient.…”
Section: Molecular Biology Of Reticulohistiocytosesmentioning
confidence: 99%
See 3 more Smart Citations